Pengaruh self Efficacy Dan Strategi Pemasaran terhadap Peningkatan Kinerja Agen Asuransi Syariah PT. Asuransi Sinar Mas Kisaran Pada Masa Pandemi Covid-19 Tahun 2020/2021 - Safitri, Dewi; Ramadhan, Muhammad (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2023)
This study aims to determine whether self-efficacy and marketing strategy affect the performance of Islamic insurance agents PT. Sinarmas Kisaran partially and simultaneously. This type of research is a quantitative descriptive with self-efficacy and marketing strategy as independent variables and agent performance as the dependent variable. The sampling technique is a saturated sample, all agents are used as a sample totaling 48 people. The data used is primary data with a questionnaire. Data analysis techniques are Validity Test and Reliability Test, Classical Assumption Test (Normality Test, Heteroscedasticity Test, Multicollinearity Test), Multiple Linear Test and Hypothesis Test (t test, F test, R2 test. Based on the statistical test results it can be concluded that partially Self Efficacy has an effect but not significant on the performance of the insurance agent PT Sinarmas Kisaran with a t-count value of 0.493 <t table (1.6772) and a significance of 0.624 > 0.05. Partially the Marketing Strategy has an effect on the performance of the insurance agent PT. Sinarmas Kisaran with a magnitude tcount value of 6.728> t table (1, 6772) and significance at 0.000 <0.05 Simultaneously Self Efficacy and Marketing Strategy affect the performance of insurance agents PT Sinarmas Kisaran with fcount value 44.760 > F table 2.81 or a significant value produced 0.000 <level of significant 0.05. R Square value of 0.665 this means that the influence of Self Efficacy (X1) and Government Strategy the target (X2) simultaneously affects performance (Y) is 66.50%. Keywords : Self Efficacy, Marketing Strategy, Agent Performance